Herbivory control over tundra carbon storage under climate change - Ylänne, H. (Henni) (Oulun yliopisto, 2017)
Abstract Air temperatures in high-latitude regions are anticipated to rise by several degrees by the end of the century and result in substantial northward shifts of species. These changes will likely affect the source and sink dynamics of greenhouse gases and possibly lead to a net carbon release from high-latitude soils to the atmosphere. However, regional differences in carbon cycling depend highly on the vegetation community composition, which may be controlled by the abundance of herbivores. I investigated whether mammalian herbivores, mainly reindeer and rodents, alter ecosystem carbon storage through their impacts on vegetation and on dominant plant functional traits. I combined observations of recent changes in ecosystem carbon with experimental field manipulations of both herbivory and climate change and measured carbon storage in vegetation and soil, the uptake and release of carbon dioxide, microbial activity and compared these to plant community composition. Results of my PhD thesis show that under ambient conditions, the impacts of herbivory on both above- and belowground carbon storage ranged from positive to negative. Herbivory altered dominant plant functional traits and these were fairly good predictors of the changes in soil carbon. When combined with experimental warming, herbivory continued to exert control on the dominant plant functional traits but the strong effects of warming on ecosystem carbon storage mostly concealed the impact of herbivory. Interestingly, herbivory–nutrient interactions that were not linked to dominant functional traits determined the consequences of warming on soil carbon. Taken together, I show clear and site-specific impacts of herbivores on vegetation and ecosystem carbon storage and the processes that govern them. Therefore, I suggest that an improved understanding of the role of herbivory in the global carbon cycle could improve estimations of global carbon–climate feedbacks. Tiivistelmä Vuosisadan loppuun mennessä arktisten alueiden lämpötilan odotetaan ...